THE EFFECT OF CAPITAL ADEQUACY RATIO AND GOOD CORPORATE GOVERNANCE ON NON-PERFORMING FINANCING WITH GROSS DOMESTIC PRODUCT AS MODERATION IN SHARIA BANKING IN INDONESIA - ILHAM HABIBI ZAKARIA (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to analyze the effect of capital adequacy ratio (CAR) and good corporate governance (GCG) on non-performing financing (NPF) with the gross domestic product (GDP) as a moderating variable in Islamic banking in Indonesia. The object of research is Islamic commercial banks in Indonesia with an observation period of 2016-2021, using a purposive sampling technique. The analytical method used is panel data regression analysis and moderate regression analysis (MRA), with the selected model testing being the fixed effect model (FEM). The analysis results show that CAR, GCG, and PDB simultaneously significantly affect NPF. The partial analysis results show that CAR has a negative and significant effect on NPF. However, GCG has a positive and significant effect on NPF. Furthermore, GDP is proven to have no effect in moderating the relationship between CAR and GCG on NPF. The presence or absence of GDP does not affect banking financing activities. GDP is only representative of the macroeconomic conditions of society.